OPTIMALISASI PEMANFAATAN LIMBAH ORGANIK DAN ANORGANIK UNTUK MEWUJUDKAN GO GREEN CONCEPT DI DESA BUMI RAHAYU - Budiarti, Ika Niswatin; Sabbina, Fauziah Asma; Hairyanti, Rizka; Widodo, Sri; Hidayat, Syaiful (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Bumi Rahayu Village is one of the villages that had a TPS3R built in 2018 in Bulungan Regency, North Kalimantan. The utilization and processing of waste carried out by TPS3R is still not optimal. So it is necessary to make efforts to optimize the use of organic and inorganic waste with the aim of increasing income, reusing waste for community needs through the use of organic and inorganic waste. Apart from that, this activity also aims to encourage people's lifestyles to be more environmentally friendly, where people become more concerned about the surrounding environment by reducing the level of pollution and waste thrown away. The method used in this activity is training in processing organic waste from palm oil into organic fertilizer, and using inorganic waste (plastic waste) to make ecobrick innovations in the form of sofas. The result of this activity is to increase the knowledge and skills of the community in optimizing the use of organic and inorganic waste so that they can realize the go green concept in Bumi Rahayu village.